“New Horizons in T2DM Management: A Review of Emerging Antidiabetic Medications” (Faridpur Medical College Journal, 2025)
T2DM mellitus continues to pose a significant global health challenge, with rising prevalence and associated complications necessitating novel therapeutic strategies. The emerging pharmacotherapies offer a new hope that focuses on recent advancements beyond traditional glucose-lowering medications to address not only glycemic control but also the broader range of complications and comorbidities associated with diabetes mellitus.An optimal treatment for T2DM should address insulin resistance, obesity, and hyperglycemia. The next-generation GLP-1 receptor agonists, amylin analogues, and dual and triple incretin co-agonists targeting GLP-1, GIP, and glucagon receptors are effective for better glycemic control and weight loss. SGLT2 inhibitors show extended cardiometabolic and renal benefits, and the novel agent like imeglimin modulate mitochondrial dysfunction and improve insulin signaling pathways.The purpose of this article is to review the existing literature and current clinical trials showing the effectiveness and safety of these newer agents individually, as well as to explore areas of future development in the field of T2DM management.Faridpur Med. Coll. J. 2025;20(2):44-52